Preserving and enhancing mitochondrial function after stroke to protect and repair the neurovascular unit: novel opportunities for nanoparticle-based drug delivery - Novorolsky, Robyn J.; Kasheke, Gracious D. S.; Hakim, Antoine; Foldvari, Marianna; Dorighello, Gabriel G.; Sekler, Israel; Vuligonda, Vidyasagar; Sanders, Martin E.; Renden, Robert B.; Wilson, Justin J.; Robertson, George S. (Frontiers in Cellular Neuroscience, 2023)
The neurovascular unit (NVU) is composed of vascular cells, glia, and neurons that form the basic component of the blood brain barrier. This intricate structure rapidly adjusts cerebral blood flow to match the metabolic needs of brain activity. However, the NVU is exquisitely sensitive to damage and displays limited repair after a stroke. To effectively treat stroke, it is therefore considered crucial to both protect and repair the NVU.Mitochondrial calcium (Ca2+) uptake supports NVU function by buffering Ca2+ and stimulating energy production. However, excessive mitochondrial Ca2+ uptake causes toxic mitochondrial Ca2+ overloading that triggers numerous cell death pathways which destroy the NVU. Mitochondrial damage is one of the earliest pathological events in stroke. Drugs that preserve mitochondrial integrity and function should therefore confer profound NVU protection by blocking the initiation of numerous injury events. We have shown that mitochondrial Ca2+ uptake and efflux in the brain are mediated by the mitochondrial Ca2+ uniporter complex (MCUcx) and sodium/Ca2+ /lithium exchanger (NCLX), respectively. Moreover, our recent pharmacological studies have demonstrated that MCUcx inhibition and NCLX activation suppress ischemic and excitotoxic neuronal cell death by blocking mitochondrial Ca2+ overloading. These findings suggest that combining MCUcx inhibition with NCLX activation should markedly protect the NVU. In terms of promoting NVU repair, nuclear hormone receptor activation is a promising approach. Retinoid X receptor (RXR) and thyroid hormone receptor (TR) agonists activate complementary transcriptional programs that stimulate mitochondrial biogenesis, suppress inflammation, and enhance the production of new vascular cells, glia, and neurons. RXR and TR agonism should thus further improve the clinical benefits of MCUcx inhibition and NCLX activation by increasing NVU repair. However, drugs that either inhibit the MCUcx, or stimulate the NCLX, or activate the RXR or TR, suffer from adverse effects caused by undesired actions on healthy tissues.To overcome this problem, we describe the use of nanoparticle drug formulations that preferentially target metabolically compromised and damaged NVUs after an ischemic or hemorrhagic stroke. These nanoparticle-based approaches have the potential to improve clinical safety and efficacy by maximizing drug delivery to diseased NVUs and minimizing drug exposure in healthy brain and peripheral tissues.